Resonant cavity-enhanced devices on Au/Si substrate - Manibog, Kristine Inocente
Two InxGa1-xAs/GaAs based resonant cavity-enhanced (RCE) devices employing external mirrors were grown by Molecular Beam Epitaxy. One is a conventional p-i-n structure and the other layer is integrated with 24-period top distributed Bragg reflectors (DBR). Epitaxial lift-off (ELO) and wafer-bonding techniques were employed to the two RCE devices by selectively etchning the AIAs sacrificial layer using a 10% hydrofluoric acid solution in water. The ELO RCE devices were transferred in highly reflective Au-coated host substrates. Drastic enhancements in the quantum efficiencies of the ELO RCE devices were observed as compared to the conventional device. The integration of the highly reflective external gold mirror significantly improves the resonant cavity-effect of the devices. Moreover, the inclusion of a top DBR mirror further enhances the wavelength selectively detection of the devices.